‘Kayuhan Merdeka UMP’ Programme highlighted the Merdeka Month Celebration - Pejabat, Naib Canselor UMP
1. MoU signed between UMP and Hassan II University of Casablanca 2. UMP welcomes 2,104 new students 3. 1,000 trees planted to fight against global warming 4. ‘Kayuhan Merdeka UMP’ Programme highlighted the Merdeka Month Celebration